Souls in Transition: The Religious and Spiritual Lives of Emerging Adults - Flory, Richard (Sociology of religion, 2011)
Several books have been written over the past few years that have analyzed different aspects of “youth religion.” These range from studies that focus on different religious expressions of the so-called “X,” “Millennial,” or otherwise Post-Boomer generations, to others that are focused on particular innovative and youth-oriented congregations. With Souls in Transition, we not only get an excellent addition to the literature on young adult religion, but an update on how the teens we first met in Soul Searching (Smith and Denton 2005) are faring in their religious and spiritual lives, and what that might say about the state of religion in American society and culture more broadly.